Identifying Predictive Level of Self-esteem in Self- handicapping in Champion and Non-champion Athlete students in Physical Education and Sport Science College - Leila Sabeghi; Esmat Danesh; Hossein Rezabakhsh; Narguesse Salliminia (روانشناسی بالینی و شخصیت, 2015)
This paper aims to identify and compare level of self-esteem in self- handicapping in champion and non-champion athlete students in Physical Education and Sport Science College. The methodology for this research is post-event and statistical population was 975 students in Physical Education and Sport Science College in Azad University of Karaj in 2011-2012 academic year in which 115 students were selected based on gender, academic major and championship status using stratified sampling and Borg and Gal sample estimation formula. The survey tools were Jones and Rhodewalt self- handicapping and Rosenberg self-esteem questionnaires. The data were analyzed using single-variable two-way variance, correlation coefficient and single-variable regression. Findings showed more self-esteem for champion athlete students compared to those without any silverware. But no significant difference was observed for self-esteem and self-handicapping level between female and male champion and non-champion athletes. The relationship between self-esteem and self-handicapping for male athletes was stronger than that of females while the relationship between self-handicapping and self-esteem was vice versa. Findings showed that self-esteem and self-handicapping could predict each other. And since reverse relationship between self-esteem and self-handicapping in non-champion was stronger than that of champion students, self-esteem and self-empowerment could be improved by providing bases for achievements.